Pengaruh Physical Distancing Dan Keamanan Konsumen Terhadap Minat Beli Produk Sepatu Bata Dengan Kualitas Pelayanan Protokol Kesehatan Sebagai Moderating - Harris Manurung; Fais Datul Fidad Nurul Islam (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2020)
Knowing the application of physical distancing and consumer safety to purchases with quality service. This study aims to examine and analyze the effect of physical distancing and consumer safety on buying interest in brick products with the quality of health protocol services as a moderating variable. The population in this study were all brick product consumers at Bata Sunter Mall in Jakarta. The data collection technique uses random sampling by distributing questionnaires via Google Form and Whatsapp.Keywords: Physical distancing, consumer safety, interest in buying brick products, quality of health protocol services.